2009
DOI: 10.1097/tp.0b013e31819d340f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Graft-Versus-Host Disease on Skin Endothelial and Epithelial Cell Chimerism in Stem-Cell Transplant Recipients

Abstract: From these results, we conclude that donor-derived endothelial cell chimerism results from repair of damaged endothelium and maintenance of vascular homeostasis. In contrast, epithelial cell chimerism follows a more uniform pattern of engraftment, not influenced by tissue damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…43 In our study, we found very few donor-derived endothelial cells in the BM, with the exception of one patient, whose microvessels had a higher number of donor-derived endothelial cells. This patient was the only patient in our cohort who lacked an HLA-identical sibling or a matched unrelated donor and therefore received a haploidentical, T cell-depleted allo-HSCT from his mother.…”
Section: Discussionmentioning
confidence: 77%
“…43 In our study, we found very few donor-derived endothelial cells in the BM, with the exception of one patient, whose microvessels had a higher number of donor-derived endothelial cells. This patient was the only patient in our cohort who lacked an HLA-identical sibling or a matched unrelated donor and therefore received a haploidentical, T cell-depleted allo-HSCT from his mother.…”
Section: Discussionmentioning
confidence: 77%
“…[37][38][39] These studies used a combination of XY FISH and immunostaining in skin or gut biopsies from sex-mismatched female transplant recipients (with male donors). In skin biopsy samples ECs of donor origin were considerably increased in patients with GVHD.…”
Section: Neovascularization During Gvhdmentioning
confidence: 99%
“…Two earlier studies, which did not find donor-type endothelial cells in the stromal constituents of bone marrow up to 3 years after HSCT, 29,30 were contrasted by several reports showing endothelial cell chimerism in skin, gut, heart and bone marrow after gender-mismatched HSCT. [14][15][16][17][18]31,32 All these studies used XY in situ hybridization for the detection of donor-derived cells. Reported numbers of donor-type bone marrow-derived endothelial cells after HSCT varied from 2% in non-GVHD-affected skin and gastrointestinal tract up to 40% in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, the maximal percentage of chimeric endothelial cells was 9.5% during the effector phase of acute GVHD, but, after this phase, the proportion of chimeric cells fell to 2%. Furthermore, Willemeze et al 18 recently reported even higher percentages of donorderived endothelial cell chimerism (up to 25% in skin biopsies) related to both repair of damaged endothelium and maintenance of vascular homeostasis; in contrast, skin epithelial cell chimerism (85%) did not seem to correlate with tissue damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation